WHAT HAPPENS IF THE BROMELAIN IN Ananas comosus L. Merr. GIVEN TO PEOPLE LIVING WITH HIV/AIDS (PLWHA) ? : A REVIEW - Reni Hariyanti; Sri Sumarni (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Human immunodeficiency virus /Acquired immunodeficiency syndrome (HIV/AIDS) is a global problem that requires serious treatment. Antiretroviral therapy (ART) has the potential to cause side effects and drug resistance for people living with HIV/AIDS (PLWHA). Alternative therapies using combination of bromelain and ART to maintain and improve immunity of PLWHA. The objective of the study was to describe the potential of bromelain in pineapple (Ananas comosus (L.) Merr) to increase the immune system of people living with HIV/AIDS. Methodology: The research method used a systematic literature review. The literature that this study used was search through in the Science Direct and Google Schoolar database. The article search used the keyword Ananas comosus (L.) Merr, HIV/AIDS healing pathway or bromelain enzyme healing pathway HIV/AIDS and Pineapple "bromelain enzyme" for HIV/AIDS. Obtained 4 articles from 219 articles published between 2010 until 2019. The article used in this study written in English and Indonesian. Results: The results showed that the bromelain enzyme in pineapple have proteolytic properties that can destroy the protein layers of the HIV viruses. The other benefit are immunomodulators that can increase the immune system of PLWHA by increasing CD4 counts or maintaining the stability of the CD4 count and reducing viral load levels even undetectable. Conclusion: The conclusion of this study is bromelain in pineapple can be used as an alternative cure for PLWHA which do not have side effect and can destroy the HIV virus protein layer and increasing the immune system of PLWHA as well.